Content Analysis on Facebook Posts to Test Hofstede’s Scores Consistency - Tigor Nirman Simanjuntak (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2022)
Hofstede’s cultural dimensions theory has gained significant popularity since its launch around 40 years ago. Many cross-cultural literatures rested on this theory. However, along with the development of social research, this theory has been a target for criticisms about its methodology, nature, size, inconsistency, and outdated data. Therefore, this study aims to test the consistency of the cultural dimension’s theory, especially Hofstede’s national culture score. Quantitative content analysis was employed in 600 contents posted on Facebook accounts of several universities in Australia and Indonesia to see the polarization of the cultural dimensions, which were compared with Hofstede’s score. The Mann-Whitney U-test was also carried out to see the significance of polarization in each dimension. The results of this study confirmed the inconsistency of Hofstede’s cultural dimension score in one of six main findings. The implications of the findings are also discussed in relation to several criticisms of this theory.